Hydrogen uptake properties of a nanoporous PIM-1–polyaniline nanocomposite polymer. Issue 39 (24th September 2019) - Ramimoghadam, Donya; Brown, Christopher L.; Boyd, Sue E.; Gray, Evan MacA.; Webb, Colin J.
Abstract : The hydrogen storage behaviour of a PIM-1–polyaniline nanocomposite was studied for the first time at both ambient and cryogenic temperature. Abstract : The hydrogen storage behaviour of a PIM-1–polyaniline nanocomposite was studied for the first time at both ambient and cryogenic temperature. The porosity of the polymers was investigated using nitrogen sorption measurements. A high BET surface area of 875 m 2 g −1 was obtained for the synthesised PIM-1. Though the BET surface area decreased upon doping the PIM-1 with PANi, the mean micropore size decreased and micropore volume increased. Maximum excess hydrogen uptake capacities of 2.3 ± 0.5 wt% (298 K and 316 bar) and 6.5 ± 0.3 wt% (77 K and 110 bar) were demonstrated. These results are a significant improvement over the hydrogen uptake of either of the constituent polymers, and this has been attributed to a combination of the active sites present in polyaniline and the microporous nature of PIM-1.